Escalation and de-escalation of mechanical circulatory support in cardiogenic shock. (27th March 2021) - Bertoldi, Letizia F; Delmas, Clement; Hunziker, Patrick; Pappalardo, Federico
Abstract: Cardiogenic shock (CS) is a clinical entity that includes a wide spectrum of different scenarios. Mechanical circulatory support (MCS) plays a fundamental role in the contemporary treatment of CS, and device selection is a key element in determining optimal treatment in this complex population. Cardiac support with mechanical devices should allow reduction and complete weaning from inotropes. Persistence of elevated left ventricular (LV) filling pressures, pulmonary congestion, metabolic decompensation, and end-organ damage during current MCS are criteria for MCS escalation. Precise diagnosis of the underlying cause of right ventricular ( RV ) failure is fundamental for undertaking the correct escalation strategy. In the setting of both MCS escalation and de-escalation, it is important to select a strategy in relation to long-term perspectives (bridge-to-recovery, bridge-to-LV assist device, or bridge-to-heart transplantation). Small retrospective studies have demonstrated that the BiPella approach is feasible, reduces cardiac filling pressures and improves cardiac output across a range of causes of CS. Simultaneous LV and RV device implantation and lower RV afterload may be associated with better outcomes in biventricular CS, but prospective studies are still required.